2022-RA-1407-ESGO Variation in outcome reporting in studies of fertility sparing surgery for cervical cancer: a systematic review. (20th October 2022) - Yong, Nathanael; Cooper, Natalie; Yorke, Sarah; Baran, Chawan; Khan, Khalid; Tan, Alex; Sideris, Michail; Iliodromiti, Stamatina; Manchanda, Ranjit
Abstract : Introduction/Background: Cervical cancer affects 3, 197 UK-women and 570, 000 women worldwide annually, with peak incidence seen between 30–34 years age. For many, fertility-sparing surgery is an appealing option where possible. However, absence of large-scale data, along-with a notable variation in reported outcomes in relevant studies may undermine future efforts for consistent evidence synthesis. We aimed to systematically review the reported outcomes measured in studies that include women who underwent fertility-sparing surgery for cervical cancer and identify whether variation exists. Methodology: We searched MEDLINE, EMBASE, and CENTRAL from inception to February 2019. We included randomised controlled trials, cohort and observational studies, and case studies of more than 10 participants from January 1990 to date. We extracted data on study characteristics and all reported treatment outcomes. Results: 104 studies with a sum of 9535 participants were identified. Most studies reported on oncological outcomes (97/104), followed by fertility and pregnancy (86/104), post-operative complications (74/104), intra-operative complications (72/104), and quality-of-life (5). There was huge variation and heterogeneity in reported outcomes, with only 12% being good quality and 87% being of poor quality. Conclusion: There is significant heterogeneity in the reported outcomes. An agreed Core Outcome Set (COS) is necessary for future studies to effectively harmonise reported outcomes that are measurable and relevant to patients, clinicians, and researchers. This systematic-review sets the groundwork for the development of a COS for fertility sparing surgery in cervical cancer.